The siberian exile system - Dean, George Adam (My University, 1895)
Introduction: To open your eyes and display before them the sufferings that are hidden behind the three words, “Siberian Exile System,” would be far beyond any power of mine. Going back three centuries, we find historical records furnishing us evidence that exiles were compelled to travel through dense forests, to climb steep mountains, and to cross wild rivers to a land now known as Siberia, the land of the exiles, and there they were to build for themselves the cells, that must be their graves.
Citation: Dean, George Adam. The siberian exile system. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Siberian exile system; Suffering; Siberia; Theses; Manuscripts (documents)